Pengaruh Pengunaan Media Flipbook dengan Pendekatan STEAM Terhadap Literasi SAINS - Putu Iwan Tri Susila; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
The purpose of this study was to analyze the effect of using flipbook media with the STEAM approach on scientific literacy. The type of research used is quasi-experimental research or quasi-experimental research using the Pretest-Posttest Control Group Design. The design of this study was through several processes, namely the pretest, the implementation of learning in the experimental class and the control class and the implementation of the posttest. The types of data used are quantitative and qualitative data using instruments in the form of interviews, needs analysis questionnaires, question instruments, expert validation sheets and user response questionnaires. The use of flipbook media with the STEAM approach has a significant effect on scientific literacy skills in the competency aspect. The average results of competency aspects of scientific literacy in the control class were (85.45). The average results of the competence aspect of scientific literacy in the experimental class were (89.78). The effect size value is (0.91) if the percentage is (82%) in the large category. The use of flipbook media with the STEAM approach can improve scientific literacy skills in context, content and competency aspects in large categories.